Application of a constraints-led approach to pedagogy in schools: embarking on a journey to nurture physical literacy in primary physical education. (4th March 2019) - Roberts, William M.; Newcombe, Daniel J.; Davids, Keith
ABSTRACT: Background: Oversimplified, reductionist approaches to operationalising Physical Literacy (PL) have been a barrier to the development of a complex, dynamic and embodied understanding of the individual Physical Literacy journey. Further, there has been no appropriate approach that might allow practitioners to integrate Physical Literacy in Physical Education (PE). Whilst popular approaches, such as Teaching Games for Understanding (TGfU) and Game Sense (GS), for operationalising learner-centred and problem-based learning, have gained professional traction in the last three decades, the development of a comprehensive theoretical basis to underpin pedagogical principles has been neglected – particularly in Physical Education. Pedagogical approaches grounded in play have gained popularity as a vehicle for Physical Literacy development in Physical Education. Despite the prominence of a Constraint-Led Approach (CLA) in sport pedagogy to assist in developing 'the intelligent, autonomous individual' in sport, application to Physical Education is limited. Purpose: In this article, we propose key pedagogical principles of a Constraints-Led Approach (CLA) in primary physical education, underpinned by the theoretical framework of Ecological Dynamics (ED). Driven by the challenge of designing affordance landscapes for learning, we present our reflections on a recently designed PE curriculum for primary schools, Boing, which could facilitate the development of movement capacities in play-based curricula designed to nurture the Physical Literacy journey for individuals. An articulation of support for the key theoretical ideas is provided in this paper. Design: This is achieved through reflections on the play-based curriculum (BOING) founded on the principles of Ecological Dynamics (ED) underpinning a Constraints-Led approach (CLA) to better serve the implementation of a Physical Literacy focussed Physical Education in a Primary school setting based on key principles for delivery. Findings: Summarising the findings, the we were able to highlight the importance of developing key principles for delivering a theoretically informed curriculum that elicits key principles of Physical Literacy. Whilst movement skills are key, these approaches are able to elicit the intended outcomes in learners of confidence, motivation and competence (Whitehead 2010, 2016). Conclusions: A CLA affords the theoretical design of play-based curricula beyond just play or sport towards purposeful, inclusive learning environments . Practitioners should look to underpin their practice with key theoretical ideas. This paper is of particular interest to those coaches and teachers tasked with designing practical environments for learning beyond the rhetoric of skill development in sport.